Technology evolution for silicon nano-electronics : selected, peer reviewed papers from the proceedings of the International Symposium on Technology Evolution for Silicon Nano-Electronics 2010, June 3-5, 2010, Tokyo Institute of Technology, Tokyo, Japan - International Symposium on Technology Evolution for Silicon Nano-Electronics (2010 : Tokyo Institute of Technology); Miyazaki, Seiichi; Tabata, Hitoshi (Stafa-Zurich, Switzerland ; Enfield, N.H. : Trans Tech Publications, 2011)
Silicon ultra-large scale integrated circuits (ULSIs) are now faced with various physical limits to further scaling. Therefore, it is very important to establish the fundamental science and technology required to produce nano-scale complementary metal-oxide-semiconductor devices (Nano-CMOS) having high performance, new functionalities and larger-scale integration. The scope of this book covers: - Nano-scale complementary metal-oxide-semiconductor devices (Nano-CMOS), - Novel functional devices, materials, and nanoprocessing technologies, - Nano-bio physics and technologies for future nano devices, - Variability control technologies and Signal integrity. This makes it a very useful handbook on the subject. Review from Book News Inc.: The 38 selected and peer-reviews papers gathered here explore possible directions now that silicon-based semiconductors are running up against physical limits to further miniaturization. They cover nano-structure physics and nano-material science, nano-processing and nano-devices, nano-system functionality integration, and nano-device integrity for variability and fluctuation and management and integration. Among the topics are photoluminescence characteristics of ultra-thin silicon-on-insulators at low temperature, the nano-surface modification of silicon with an ultra-short pulse laser process, the microscopic structure of directly bonded silicon substrates, and analyzing threshold voltage variations in fin field effect transistors.
High Mobility Ge-Based CMOS Device Technologies -- SiGe-Mixing-Triggered Rapid-Melting-Growth of High-Mobility Ge-On-Insulator -- Impact of Self-Heating Effect on the Electrical Characteristics of Nanoscale Devices -- Functional Device Applications of Nanosilicon -- Tunable Single-Electron Turnstile Using Discrete Dopants in Nanoscale SOI-FETs -- KFM Observation of Electron Charging and Discharging in Phosphorus-Doped SOI Channel -- Photoluminescence Characteristics of Ultra-Thin Silicon-on-Insulator at Low Temperatures -- Investigation about I-V Characteristics in a New Electronic Structure Model of the Ohmic Contact for Future Nano-Scale Ohmic Contact -- Collective Electron Tunneling Model in Si-Nano Dot Floating Gate MOS Structure -- Electronic Structure and Spin-Injection of Co-Based Heusler Alloy/ Semiconductor Junctions -- First-Principles Calculations of the Dielectric Constant for the GeO2 Films -- Nanosize Electronics Material Analysis by Local Quantities Based on the Rigged QED Theory -- Novel Source Heterojunction Structures with Relaxed-/Strained-Layers for Quasi-Ballistic CMOS Transistors -- Effect of Al2O3 Deposition and Subsequent Annealing on Passivation of Defects in Ge-Rich SiGe-on-Insulator -- Controlled Synthesis of Carbon Nanowalls for Carbon Channel Engineering -- Resistive Memory Utilizing Ferritin Protein with Nano Particle -- Atomically Controlled Plasma Processing for Group IV Quantum Heterostructure Formation -- Nanometer-Scale Characterization Technique for Si Nanoelectric Materials Using Synchrotron Radiation Microdiffraction -- Generation and Growth of Atomic-Scale Roughness at Surface and Interface of Silicon Dioxide Thermally Grown on Atomically Flat Si Surface -- Nano-Surface Modification of Silicon with Ultra-Short Pulse Laser Process -- Evaluation of Strained Silicon by Electron Back Scattering Pattern Compared with Raman Measurement and Edge Force Model Calculation -- Development of New Methods for Fine-Wiring in Si Using a Wet Catalytic Reaction -- Optical Response of Si-Quantum-Dots/NiSi-Nanodots Stack Hybrid Floating Gate in MOS Structures -- Energy Band Engineering of Metal Nanodots for High Performance Nonvolatile Memory Application -- Strained Ge and Ge1-xSnx Technology for Future CMOS Devices -- Improved Electrical Properties and Thermal Stability of GeON Gate Dielectrics Formed by Plasma Nitridation of Ultrathin Oxides on Ge(100) -- Structural Change during the Formation of Directly Bonded Silicon Substrates -- Microscopic Structure of Directly Bonded Silicon Substrates -- Formation of Nanotubes of Carbon by Joule Heating of Carbon-Contaminated Si Nanochains -- Si Nanodot Device Fabricated by Thermal Oxidation and their Applications -- Influences of Carrier Transport on Drain-Current Variability of MOSFETs -- Resistive Switching in NiO Bilayer Films with Different Crystallinity Layers -- Analysis of Threshold Voltage Variations in Fin Field Effect Transistors -- Capture/Emission Processes of Carriers in Heterointerface Traps Observed in the Transient Charge-Pumping Characteristics of SiGe/Si-Hetero-Channel pMOSFETs -- Quasi-Ballistic Transport in Nano-Scale Devices: Boundary Layer, Potential Fluctuation, and Coulomb Interaction -- Effect of Back Bias on Variability in Intrinsic Channel SOI MOSFETs -- Discrete Dopant Effects on Threshold Voltage Variation in Double-Gate and Gate-All-Around Metal-Oxide-Semiconductor Field-Effect-Transistors -- Interconnect Design Challenges in Nano CMOS Circuit.
Includes bibliographical references and indexes.
Keywords: Nanoelectronics -- Congresses; Nanostructured materials -- Congresses; Metal oxide semiconductors -- Congresses